2017
DOI: 10.1038/mp.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

GLRB allelic variation associated with agoraphobic cognitions, increased startle response and fear network activation: a potential neurogenetic pathway to panic disorder

Abstract: The molecular genetics of panic disorder (PD) with and without agoraphobia (AG) are still largely unknown and progress is hampered by small sample sizes. We therefore performed a genome-wide association study with a dimensional, PD/AG -related anxiety phenotype based on the Agoraphobia Cognition Questionnaire (ACQ) in a sample of 1,370 healthy German volunteers of the CRC TRR58 MEGA study wave 1. A genome-wide significant association was found between ACQ and single non-coding nucleotide variants of the GLRB g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 71 publications
1
46
1
1
Order By: Relevance
“…The time window of 1‐hour preincubation with the patient GlyR autoantibodies is accompanied by an internalization rate of 30% of surface GlyRs (data not shown). A reduction by 30% of cell surface receptors usually does not change maximal current amplitudes as demonstrated by whole‐cell recordings from cells transfected with GlyRα1 mutants associated with hyperekplexia 32 . No significant changes in whole‐cell maximum currents were found following application of a saturating glycine concentration (1mM; see Fig 2D).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The time window of 1‐hour preincubation with the patient GlyR autoantibodies is accompanied by an internalization rate of 30% of surface GlyRs (data not shown). A reduction by 30% of cell surface receptors usually does not change maximal current amplitudes as demonstrated by whole‐cell recordings from cells transfected with GlyRα1 mutants associated with hyperekplexia 32 . No significant changes in whole‐cell maximum currents were found following application of a saturating glycine concentration (1mM; see Fig 2D).…”
Section: Resultsmentioning
confidence: 81%
“…One‐hour incubation with the GlyR autoantibody resulted in receptor internalization of about 30 to 50% 4 . Current knowledge from GlyRα1 mutant receptors associated with hyperekplexia 32 revealed that a reduction by 30 to 50% of cell surface receptor protein does usually not change maximal current amplitudes. If, however, the GlyR protein is reduced by >85%, a decrease in glycine‐gated chloride current amplitudes at maximal glycine concentrations would be expected 33,45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Eighty‐one participants were selected from a larger sample of healthy volunteers recruited within the framework of the collaborative research center SFB TRR58 (Deckert et al, ; Schartner et al, ; Schiele et al, ). BDNF rs6265 was genotyped using standard PCR followed by enzymatic digestion and staining according to our previously published protocol (Mühlberger et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in the genes encoding this GlyR subtype ( GLRA1 and GLRB ) cause startle disease, characterized by noise- or touch-induced non-epileptic seizures, excessive muscle stiffness and neonatal apnea episodes in cattle, mice and humans (Harvey et al, 2008; Bode and Lynch, 2014). Allelic variants of GLRB have also recently been associated with agoraphobic behavior, an increased startle response and fear network activation (Deckert et al, 2017). …”
Section: Introductionmentioning
confidence: 99%